Anxiety and depression in geriatric hemodialysis patients: factors that influence the border of diseases - Elezi, Brunilda; Abazaj, Erjona; Zappacosta, Bruno; Hoxha, Malvina (Frontiers in Psychology, 2023)
The two main psychological issues that people with end-stage renal disease (ESRD) experience are depression and anxiety. We conducted this study to determine both the prevalence of depression, and anxiety, and the factors associated with them, among hemodialysis patients.Patients aged 18 years or older, who had received hemodialysis in a hemodialysis center in Elbasan, for at least three months were included in this study. Beck Anxiety Inventory and Beck Depression Inventory Instruments were used to assess hemodialysis patients levels of depression and anxiety.Overall, 107 hemodialysis patients (men 65.4%) with a mean age of 57±8.9 years were enrolled in the study. The prevalence of anxiety and depression resulted to be 85.98%, and 84.11% respectively. We found a significant difference in depression and anxiety scores in patients age groups of 61 to 70 years old (OR=1.8; 95% CI [0.7-3.7]; P=0.041), in non smoking patients (OR 3.4;; P=0.04), in diabetic patients (OR 3.4;; P=0.04), and in patients with a time in dialysis of 6-10 years and >11 years respectively (OR 3.4; 95% [1.5-9.0]; P=0.01),(OR1.3; 95% CI [0.4-3.6]; P=0.04).Our study shows that the prevalence of mental disorders (depression and anxiety) is high among patients with ESRD on maintenance hemodialysis. We recommend a routine screening and referral to psychological health specialists to evaluate the mental health disorders among hemodialysis patients with the primary aim of improving their quality of life.